Giải phương trình a ) x mũ 2 – 6x + 9 = 25 b ) 9x mũ 2 – 6x – 3 = 0 c ) x mũ 3 + 9x mũ 2 + 27x + 19 = 0

Giải phương trình
a ) x mũ 2 – 6x + 9 = 25
b ) 9x mũ 2 – 6x – 3 = 0
c ) x mũ 3 + 9x mũ 2 + 27x + 19 = 0

2 bình luận về “Giải phương trình a ) x mũ 2 – 6x + 9 = 25 b ) 9x mũ 2 – 6x – 3 = 0 c ) x mũ 3 + 9x mũ 2 + 27x + 19 = 0”

  1. Giải đáp + Lời giải và giải thích chi tiết:
     a)
    x^2-6x+9=25
    ⇔ (x-3)^2 = 25
    ⇔ (x-3)^2-25=0
    ⇔ (x-3-5)(x-3+5)=0
    ⇔ (x-8)(x+2)=0
    [x8=0x+2=0
    [x=8x=2
    Vậy S={-2;8}.
    b)
    9x^2 – 6x-3=0
    ⇔ 9x^2 – 9x+3x-3=0
    ⇔ (9x^2-9x)+(3x-3)=0
    ⇔ 9x(x-1)+3(x-1)+0
    ⇔ (x-1)(9x+3)=0
    [x1=09x+3=0
    [x=1x=13
    Vậy S={(-1)/3;1}.
    x)
    x^3 + 9x^2 + 27x + 19=0
    ⇔ (x^2+9x^2+27x+ 27 )-8=0
    ⇔ (x+3)^3 – 8=0
    ⇔ (x+3)^3=8
    ⇔ (x+3)^3=2^3
    => x+3=2
    ⇔ x=-1
    Vậy S={-1}.

    Trả lời
  2. Giải đápLời giải và giải thích chi tiết:
    a) x^2 – 6x + 9 = 25
    ⇔ (x-3)^2 = 25
    ⇔(x-3)^2 – 25 = 0
    ⇔ (x-3-5)(x-3+5) = 0
    ⇔(x-8)(x+2) = 0
    TH1 : x-8=0
    ⇔x=8
    TH2 : x+2=0
    ⇔x=-2
    Vậy S={8;-2}
    ——————————————
    b) 9x^2 – 6x – 3 = 0
    ⇔ 9x^2 – 9x + 3x – 3 =0
    ⇔9x(x-1) + 3(x-1) = 0
    ⇔(x-1)(9x +3) = 0
    TH1 : x-1=0
    ⇔x=1
    TH2 : 9x + 3=0
    ⇔9x=-3
    ⇔x=-1/3
    Vậy S={1;-1/3}
    —————————————–
    c) x^3 + 9x^2 + 27x + 19 = 0
    ⇔x^3 + 9x^2 + 27x +27 -8=0
    ⇔(x+3)^3 – 2^3 = 0
    ⇔(x+3)^3 = 2^3
    ⇔ x+3=2
    ⇔x=-1
    Vậy x=-1

    Trả lời

Viết một bình luận

Câu hỏi mới